Immunochromatographic lateral flow test for detection of antibodies to Equine infectious anemia virus - Alvarez, Irene (2010)
The purpose of this study was to develop and evaluate a simple immunochromatographic lateral flow(ICLF) test for specific detection of Equine infectious anemia virus (EIAV) antibodies in equine sera. Viral recombinant p26 capsid protein (rp26) was used as the capture protein in the test line and as the detector reagent conjugated to colloidal gold. The performance of rp26-ICLF was evaluated, and the results obtained were compared with a commercially available agar gel immunodiffusion (AGID) test used as a standard of comparison according to international guidelines. The values obtained for comparative diagnostic sensitivity (98.3%), diagnostic specificity (87.4%) and concordance (92.4%) were similar to those reported for other ICLF tests for animal infectious diseases. Very good repeatability and reproducibility, as well as a total agreement with blind previous results from three proficiency test panels, were obtained, thus indicating that rp26-ICLF is a precise test. The end point of the twofold serial dilution of serum samples was the same as, and even better than, the AGID test, thus demonstrating the same analytical sensitivity as that of the reference method for EIA diagnosis. No cross-reactivity was observed when serum samples from horses with other infectious diseases were analyzed. rp26-ICLF proved to be a precise and rapid test suitable for field screening in veterinary practice, since minimal equipment and operator expertise are required. However, further research should be carried out to increase the level of sensitivity.